2022
DOI: 10.1021/acsami.2c12029
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Self-Assembled Monolayers with Tunable Surface Dynamics for Controlling Cell Adhesion Behavior

Abstract: Cells adhering onto surfaces sense and respond to chemical and physical surface features. The control over cell adhesion behavior influences cell migration, proliferation, and differentiation, which are important considerations in biomaterial design for cell culture, tissue engineering, and regenerative medicine. Here, we report on a supramolecular-based approach to prepare reversible self-assembled monolayers (rSAMs) with tunable lateral mobility and dynamic control over surface composition to regulate cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…[79,80] Yeung et al have reported a technique that relies on supramolecular interactions to generate reversible selfassembled monolayers characterized by tunable lateral mobility and the capacity to dynamically manipulate surface composition, thereby governing cell adhesion behavior. [81] The sensing mechanism employed by this system entails the utilization of noncovalent ion pairs between amidinium and carboxylate to facilitate the creation (on) and dissolution (off) of stable 2D structures. These structures bear a resemblance to lipid bilayers but can be easily prepared and exhibit rapid on/off rates, as depicted in Figure 5A.…”
Section: Cell Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…[79,80] Yeung et al have reported a technique that relies on supramolecular interactions to generate reversible selfassembled monolayers characterized by tunable lateral mobility and the capacity to dynamically manipulate surface composition, thereby governing cell adhesion behavior. [81] The sensing mechanism employed by this system entails the utilization of noncovalent ion pairs between amidinium and carboxylate to facilitate the creation (on) and dissolution (off) of stable 2D structures. These structures bear a resemblance to lipid bilayers but can be easily prepared and exhibit rapid on/off rates, as depicted in Figure 5A.…”
Section: Cell Adhesionmentioning
confidence: 99%
“…Reproduced with permission. [ 81 ] Copyright 2022, with permission from American Chemical Society. (B) Circular dichroism spectra, schematic illustrations, and fluorescence images for 3D MSA structures.…”
Section: Applications Of Chiral Supramolecular Nanomaterialsmentioning
confidence: 99%
“…These mechanical problems restrain the scalability of the mechanical methods. Chemical and biochemical methods of cell harvesting based on changes in pH of the medium, , ion concentration, electrochemical processes, reversible self-assembled monolayers, reversible or competitive molecular recognition, and light-induced photochemical processes , are limited due to the high sensitivity of cells to the composition of the medium or high costs of the biomaterials. Even minor changes in the medium’s chemical composition, concentrations, and pH can trigger cell apoptosis or mutations.…”
Section: Introductionmentioning
confidence: 99%
“…1). rSAMs offer robust and adaptable receptors featuring strongly enhanced a nities toward proteins, 29 viruses 30 and human cells 31 compared to receptors based on stiffer scaffolds. The formation of the rSAMs is driven by the spontaneous assembly of benzamidineterminated amphiphiles on alkanoic acid functionalized surfaces (e.g.…”
Section: Introductionmentioning
confidence: 99%